Fixed-dose combinations at the front line of multimodal pain management: perspective of the nurse-prescriber - O'Brien J; Pergolizzi Jr JV; van de Laar M; Mellinghoff HU; Morón Merchante I; Nalamachu S; Perrot S; Raffa RB (Nursing: Research and Reviews, 2013)
Joanne O’Brien,1 Joseph V Pergolizzi Jr,2 Mart van de Laar3, Hans-Ulrich Mellinghoff,4 Ignacio Morón Merchante,5 Srinivas Nalamachu,6 Serge Perrot,7 Robert B Raffa81Department of Pain Medicine, Beaumont Hospital, Beaumont, Dublin, Ireland; 2Department of Medicine, Johns Hopkins University School of Medicine, Baltimore, MD; Association of Chronic Pain Patients, Houston, TX; Department of Pharmacology, Temple University School of Medicine, Philadelphia, PA, USA; 3Arthritis Center Twente, Enschede, The Netherlands; 4Department of Endocrinology, Diabetology and Osteology, Kantonsspital St Gallen, Switzerland; 5Centro de Salud Universitario Goya, Madrid, Spain; 6Kansas University Medical Center, Kansas City, and International Clinic Research, Leawood, KS, USA; 7Service de Médecine Interne et Consultation de la Douleur, Hôpital Hotel Dieu, Paris Descartes University, Paris, France; 8Department of Pharmaceutical Sciences, Temple University School of Pharmacy, Philadelphia PA, USAAbstract: Pain should be treated promptly and effectively to restore the patient to full function, avoid pain chronification, and preserve quality of life. A recent pain specialists' meeting discussed the use of different pharmacological treatment options, such as topical analgesics, nonopioid agents (such as paracetamol and nonsteroidal anti-inflammatory drugs), weak and strong opioids, and fixed-dose combination products in the management of moderate to severe pain from different etiologies. One of the topics discussed in, and subsequent to, this meeting was the role of fixed-dose combination products for nurse-prescribers who are in many ways at the front line of managing both acute and chronic pain syndromes. The panel agreed that proper product selection should take into account the patient's age, condition, type of pain, and comorbidities, as well as balance safety with effectiveness. Although nurse-prescribers need to be aware of cumulative paracetamol dosing, fixed-dose combination products, such as tramadol-paracetamol, may offer important advantages, eg, by providing opioid-sparing without sacrificing efficacy.Keywords: tramadol, paracetamol, fixed-dose combination analgesics, pain management